Pressure drop and permeability of three-dimensional virtual fibrous medium. (April 2015) - Fu, H. M.
Abstract : Pressure drop is one of the principal performances of the fibrous filtration medium. Traditional computational studies in this area are based on typical unrealistic two-dimensional geometries, with the fibre just placed in a lattice perpendicular to the flow. So in this paper, a three-dimensional virtual fibrous material was developed by means of visual basic application. In the virtual fibrous material, the fibres were arranged randomly by computer and the flow field of virtual fibrous material was calculated. The influence of constructive parameters on pressure drop and permeability was investigated. Simulation shows that flow field velocity distribution was not symmetric. Filtration velocity decreased when the air flew through the fibres, whereas the fluid velocity increased significantly when the distance between fibres was large. Obvious vortex formed in the fibre space areas. The pressure drop was tested experimentally, and the result was compared with that of theoretical and semi-empirical formula calculation. Experimental and simulation data were in agreement with Davies' empirical formula. The simulation result reveals that the pressure drop of fibrous medium increased linearly with the increase of filtration velocity. Moreover, pressure drop non-linearly increased with the increasing solid volume fraction. Simulation results of pressure drop were in good agreement with the predictions of Davies' empirical formula.